The Practice of Triple Talaq and Women's Protection in Aceh: A Maslahat Perspective - Hanapi, Agustin; Aini, Sarina; Husnul, Muhammad; Usman, Iskandar; Natasya Solin, Siti Dian (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Talaq resulting in divorce is one of the issues discussed in Islamic family law not only in Aceh, but in Indonesia and the Muslim world. This study aims to discuss triple talaq at once that occurred in Aceh in relation to women's protection. This study uses empirical legal methods, analyzed with the theory of maslahat. Data is collected by; In-depth interviews and document review. This study concluded that triple talaq occurs due to three factors; The existence of wild qadhi, the presence of muhallil, lack of understanding. These three factors cause married couples to believe that triple talaq pronounced by the husband is legally valid, even though it occurs outside the court. Talaq must also be performed before the Court whose function is as a witness for the protection of the rights of the former husband and wife. In this context, to provide awareness and socialization about the legal rules regarding marriage, synergistic cooperation between institutions and across sectors is needed. These institutions are, syar'iyah courts or religious courts, religious ministries, clerical organizations, educational institutions and religious leaders at the village level. So that an understanding of the rules of law that apply in religious courts can be conveyed to the community as a whole. Thus, the issue of triple talaq does not make the wife a victim, because the husband can easily give talaq, resulting in a divorce. In the context of benefits, these legal regulations are carried out with the aim of protecting women's rights and making them dignified and treated fairly.